2019
DOI: 10.1111/nph.15665
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of TNL‐mediated immune signaling by redundant helper CNLs

Abstract: Summary Higher plants utilize nucleotide‐binding leucine‐rich repeat domain proteins (NLRs) as intracellular immune receptors to recognize pathogen‐derived effectors and trigger a robust defense. The Activated Disease Resistance 1 (ADR1) family of coiled‐coil NLRs (CNLs) have evolved as helper NLRs that function downstream of many TIR‐type sensor NLRs (TNLs). Close homologs of ADR1s form the N REQUIREMENT GENE 1 (NRG1) family in Arabidopsis, the function of which is unclear. Through CRISPR/Cas9 gene editing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

26
315
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(341 citation statements)
references
References 64 publications
26
315
0
Order By: Relevance
“…However, the requirement of NRG1 by RPP1, RPP2 and RPP4 for downy mildew resistance, although significant, is weak. In addition, RPP4 function was not affected in an independent experiment (Wu et al ., ). Thus, other helpers, such as ADR1 family proteins, already reported to contribute to RPP4 function (Bonardi et al ., ), also probably contribute to RPP1, RPP2 and RPP4 function.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the requirement of NRG1 by RPP1, RPP2 and RPP4 for downy mildew resistance, although significant, is weak. In addition, RPP4 function was not affected in an independent experiment (Wu et al ., ). Thus, other helpers, such as ADR1 family proteins, already reported to contribute to RPP4 function (Bonardi et al ., ), also probably contribute to RPP1, RPP2 and RPP4 function.…”
Section: Discussionmentioning
confidence: 97%
“…Here, we found that CHS3‐induced HR requires NbNRG1 . Moreover, the chs3‐2D autoimmune phenotype is completely lost in an nrg1a‐nrg1b‐nrg1c mutant of Arabidopsis (Wu et al ., ). Thus, CHS3 signals only via NRG1s.…”
Section: Discussionmentioning
confidence: 97%
“…In Arabidopsis, there are three ADR1 homologs (ADR1-L1, -L2, -L3) and two NRG1 homologs (NRG1.1, NRG1.2) (Bonardi et al, 2011;Collier et al, 2011). Indeed, NRG1 homologs were recently reported to function redundantly in TNL-mediated immunity in Arabidopsis, and also ADR1s are required for several TNL-mediated immune responses (Dong et al, 2016;Castel et al, 2018;Wu et al, 2018). Helper CNLs of the NRG1 class are critical for function of most TNLs, but others require ADR1 class helpers or can signal via both pathways (Castel et al, 2018;Wu et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, NRG1 homologs were recently reported to function redundantly in TNL-mediated immunity in Arabidopsis, and also ADR1s are required for several TNL-mediated immune responses (Dong et al, 2016;Castel et al, 2018;Wu et al, 2018). Helper CNLs of the NRG1 class are critical for function of most TNLs, but others require ADR1 class helpers or can signal via both pathways (Castel et al, 2018;Wu et al, 2018). While genetic redundancy explains failure to isolate respective mutant alleles by forward genetics, a physical association of NRG1 proteins with EDS1 as reported by Qi et al (2018) will require further analysis.…”
Section: Discussionmentioning
confidence: 99%
“…This sub-family of NLRs often have only a few members but exists in almost all plants (Zhong & Cheng, 2016). At least in angiosperms, these RPW8-NLRs are helper NLRs required for signalling of multiple sensor NLRs (Peart et al, 2005;Bonardi et al, 2011;Dong et al, 2016;Qi et al, 2018;Adachi et al, 2019;Castel et al, 2019a;Wu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%